2013
DOI: 10.9790/0853-0615154
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Alkaoids Content of Some Selected Nigerian Vegetables during Processing

Abstract: Alkaloids, natural

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
(15 reference statements)
0
2
2
Order By: Relevance
“…Pyridine was the most concentrated alkaloid subgroup. The total alkaloid content of fluted pumpkin grown in varying proportion of NPK was higher compared to other works (Onyeka and Nwambekwe, 2007;Odufuwa et al, 2013;Otitoju et al, 2014). The highest total flavonoid was obtained in M 125 NPK growth media.…”
Section: Discussioncontrasting
confidence: 58%
“…Pyridine was the most concentrated alkaloid subgroup. The total alkaloid content of fluted pumpkin grown in varying proportion of NPK was higher compared to other works (Onyeka and Nwambekwe, 2007;Odufuwa et al, 2013;Otitoju et al, 2014). The highest total flavonoid was obtained in M 125 NPK growth media.…”
Section: Discussioncontrasting
confidence: 58%
“…All the alkaloids in T. occidentalis varied in the different growth medium. The total alkaloids (11.614 g/100g NM, 9.082 g/100g HS) obtained in T. occidentalis using HPLC was higher compared to other works (Onyeka and Nwambekwe, 2007;Otitoju et al, 2014;Odufuwa et al, 2013), which reported 0.81 g/100g, 0.04 g/100g and 0.039 g/100g, respectively for total alkaloids in T. occidentalis. Also, Oduse et al (2012) reported 13.83 mg/kg for Cnidoscolus aconitifloina and 10.13 mg/kg for Vernonia amygdalina.…”
Section: Resultscontrasting
confidence: 38%
“…While the juicing is believed to concentrate the nutrients, thus, the chromium content which may also be concentrated possibly to the level that might affect the consumer adversely [12,14]. In view of the above, we set to investigate the content of chromiumin fresh vegetables and how its level is affected by juicing.…”
Section: Introductionmentioning
confidence: 99%
“…In the past consumption of fresh (unprocessed) vegetable was uncommon, but of recent the use of vegetable juice such as Telfairia occidentalis (probably for hemopoetic value) and Vernonia amygdalina (probably for antidiabetic and other therapeutic purpose) is on increase among Nigerian populace [14]. While the juicing is believed to concentrate the nutrients, thus, the chromium content which may also be concentrated possibly to the level that might affect the consumer adversely [12,14].…”
Section: Introductionmentioning
confidence: 99%